2008
DOI: 10.1016/j.physbeh.2007.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the obesity of OLETF rats

Abstract: Cholecystokinin (CCK) is a brain gut peptide that plays an important role in satiety. CCK inhibits food intake by reducing meal size. CCK's satiety actions are mediating through its interaction with CCK1 receptors. Otsuka Long Evans Tokushima Fatty (OLETF) rats are a CCK1 receptor knockout model that allows the study of multiple CCK functions. OLETF rats are hyperphagic with the hyperphagia expressed as a significant increase in the size of meals. OLETF rat obesity is secondary to the hyperphagia and has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 51 publications
1
49
0
1
Order By: Relevance
“…Thus, Otsuka Long Evans Tokushima Fatty (OLEFT) rats, which have a 6847 bp deletion within the gene for the CCK 1 receptor protein resulting in disrupted CCK 1 receptor production, present with hyperglycemia, hyperphagia, impaired glucose tolerance, and mild obesity (Moran 2008). Interestingly, in mice with genetic deletion of the CCK 1 receptor, the adverse effects are much less obvious (Bi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Otsuka Long Evans Tokushima Fatty (OLEFT) rats, which have a 6847 bp deletion within the gene for the CCK 1 receptor protein resulting in disrupted CCK 1 receptor production, present with hyperglycemia, hyperphagia, impaired glucose tolerance, and mild obesity (Moran 2008). Interestingly, in mice with genetic deletion of the CCK 1 receptor, the adverse effects are much less obvious (Bi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As such, numerous studies have shown notable therapeutic effectiveness of longer-acting CCK-based compounds (O'Harte et al 1998, Verbaeys et al 2007, 2008, 2009a. In particular, the recently characterized N-terminally modified, enzymatically stable CCK-8 analog, (pGlu-Gln)-CCK-8, causes sustained weight loss and improves both insulin resistance and glucose tolerance in mice with genetically and environmentally induced forms of obesity-diabetes (Irwin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We have characterized numerous aspects of their hyperphagia and obesity and many aspects of their development. 24 Although, the absence of CCK-1 receptor signaling is certainly not common in human obesity, there has been a single case report demonstrating obesity in an individual with such a defect, 25 the OLETF rat does share many features found in human obesity. The OLETF rat does not have a primary deficit in leptin signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the metabolic derangements seen in ob/ob mice, those in OLETF rats are entirely attributable to excess food intake (74). These rats have a defect in the satiety signal mediated by CCK1 as well as the loss of CCK1-mediated inhibition of the orexigenic neuropeptide Y in the brain.…”
Section: Overeating As a Means Of Inducing Nafldmentioning
confidence: 96%